(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Semenova O. О. Projecting method as one of the active methods of forming the functional competence of future foreign language teachers. The article describes one of the active methods of forming the functional competence of future foreign language teachers – the method of projects. The author substantiates the issues concerning the competency approach while training foreign language teachers.